Corticosteroids in peritonsillar abscess treatment: A blinded placebo‐controlled clinical trial. (9th July 2013) - Chau, Jason K. M.; Seikaly, Hadi R.; Harris, Jeffery R.; Villa‐Roel, Cristina; Brick, Craig; Rowe, Brian H.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Sore throat is a common, benign emergency department (ED) presentation; however, peritonsillar abscess (PTA) is a complication that requires aggressive management. Use of systemic corticosteroids (SCSs) in PTA is occurring without clear evidence of benefit. This study examined the efficacy and safety of SCS treatment for patients with PTA. Study Design Randomized, double‐blind, placebo‐controlled trial. Methods A controlled trial with concealed allocation and double‐blinding was conducted at two Canadian EDs. Following written informed consent, eligible patients received 48 hours of intravenous clindamycin and a single dose of the study drug (dexamethasone [DEX] or placebo [PLAC], intravenously [IV]). Follow‐up occurred at 24 hours, 48 hours, and 7 days. The primary outcome was pain; other outcomes were side effects and return to normal activities/diet. Results A total of 182 patients were screened for eligibility; 41 patients were enrolled (21 DEX; 20 PLAC). At 24 hours, those receiving DEX reported lower pain scores (1.4 vs. 5.1; P = .009); however, these differences disappeared by 48 hours (P = .22) and 7 days (P = .4). At 24 hours, more patients receiving DEX returned to normal activities (33% vs. 11%) and dietary intake (38% vs 25%); however, these differences were not significant and disappeared by 48 hours and 7 days. Side effects were rare and did not differ between groups (P > .05). Conclusions Combined with PTA drainage and IV antibiotics, 10 mg IV DEX resulted in less pain at 24 hours when compared to PLAC, without any serious side effects. This effect is short‐lived, and further research is required on factors associated with PTA treatment success. Level of Evidence 1b Laryngoscope, 124:97–103, 2014